Collaborative Writing As Educational Research: A Deleuzian Critique - David Harris (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This article discusses the claims made by some qualitative researchers that collaborative autoethnographic writing serves to displace sociology and other social sciences as a means to understand subjectivity. Collaborative creative writing claims to be no less valid than sociological inquiry and is less socially exclusive, and academic criticism of this approach is itself seen as only subjective. A particular project by Wyatt and Gale and others can still be exposed to ‘immanent critique’, however, where the philosophical resources used to support the argument (the work of Deleuze and Guattari in this case) can be explored to suggest quite different implications for subjectivity. These include discussing external social influences on creativity and collaboration, and, more generally, on subjectivity itself. Guattari’s cartography of subjectification suggests that sociological inquiry, including the sociology of education, still has a major role in providing empirical examples and experiences of the processes involved, as resources for subsequent deleuzian philosophising and for effective micropolitics.